NUMBER STICKS MEDIA FOR DEVELOPING BASIC CALCULATION SKILLS IN EARLY CHILDREN - Mohammad Archi Maulyda; Vivi Rachmatul Hidayati (Symmetry: Pasundan Journal of Research in Mathematics Learning and Education, 2020)
This study aims to determine whether or not to develop preliminary numeracy skills in Group A children TK PGRI 04 Kalibatur, Kalidawir District, Tulungagung Regency, using number stick media. This type of research is a Classroom Action Research (PTK) with a model developed by Kemmis and Mc Taggart. The subjects of this study were 13 children in group A. The data collection techniques used were observation and documentation while the instruments used were child assessment sheets and teacher observation sheets. The data analysis technique used is comparative quantitative technique. In the first cycle the percentage of completeness was 30.8%, the second cycle was 61.5%, and the third cycle was 92.3%. The conclusion of the results of this study is that learning using number stick media can develop initial numeracy skills in Group A children of TK PGRI 04 Kalibatur, Kalidawir District, Tulungagung Regency, 2020/2021Academic Year